Non-communicable diseases prevention and control by government ministries in Guyana - Roberts, Karen Rebecca Vanese; Ventura, Carla Aparecida Arena; de Sousa, Alvaro Francisco Lopes; Mendes, Isabel Amélia Costa (Frontiers in Public Health, 2024)
Background Countries of the Caribbean Community signed the Declaration of Port of Spain in 2007 with the vision to stop the epidemic of non-communicable diseases (NCDs). The adoption of the Declaration by member states represented a regional effort, challenging governments, the private sector, and civil society to act together. Multisectoral actions in Guyana aimed at achieving this goal are the focus of this article, demonstrating the work of different actors in addressing the burden of NCDs in the country. Objective To analyze multisectoral actions developed among five ministries for the implementation of the Declaration of Port of Spain 2007 in Guyana. Methods This qualitative study was guided by the Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist and conducted in five ministries (Agriculture, Education, Finance, Health, and Trade) in Georgetown, Guyana. The thematic analysis was guided by a framework consisting of four elements: context (why the policy is needed), content (what the policy is mainly about), process (how the policy was brought forward and implemented), and actors (who participates in and influences the formulation and implementation of the policy). The framework considers how these elements interconnect to shape policy development and implementation processes. Findings Data analysis provided the researchers with insights into possible topic areas and codes for consideration during the analysis, hence a deductive approach to data analysis was used. The results highlighted the importance of coordination among government entities, national and international agencies, private actors, industry players, and civil society. Participants did not mention the use of responsibility metrics but cited mechanisms that facilitated collaboration. Conclusion The results showed limitations in transforming multisectoral initiatives into intersectoral collaboration to achieve real integration among the different actors involved, considering the actual context and content. Actions could be more effectively implemented with significant outcomes for NCD control in Guyana.